Strengthening Green Taxation Within the Framework of Fulfilling the Green Deal Conditions in the Context of Formation of the Environmental Security System of EU Countries - Nikiforov, P.; Abramova, A.; Zhavoronok, А.; Bak, N.; Yaremchuk, V.; Kulynych, Yu. (International Journal of Sustainable Development and Planning, 2024)
The study is dedicated to the scientific justification of the need to strengthen green taxation in the context of the Green Deal implementation and the greening of EU countries based on a comprehensive analysis of the effective functioning of the green taxation system, and presents the following vectors of its improvement. Scientific approaches to the interpretation of the essence of the economic value of green taxation, taking into account the systematicity of the economic, socio-political, innovative and infrastructural goals in the conditions of modern challenges, have been studied. Based on the international system of economic indicators, in particular the Environmental Policy Stringency Index, the actual state of green taxation in EU countries was assessed. By applying a methodological approach based on comparing the cost characteristics of regulation and stimulation of the ecologically oriented business activity of business entities with the cost characteristics of the tax burden and the regulatory nature of the impact due to the use of environmental taxation objects and damage to the environment, an assessment of the effectiveness of green taxation was carried out in 12 EU countries. The architecture of the environmental taxation environment of EU countries is presented, the interrelated elements of which are defined as the legal framework of green taxation, the toolkit for the Green Deal implementation with an emphasis on green taxation, as well as systemically important market transformations capable of influencing the economic and environmental behavior of business entities by using natural resources and pollution of the natural environment under the influence of time factors, globalization changes and subsequent future uncertainties. The author's approach to increasing the efficiency and improvement of green taxation, which is expedient to implement to achieve the Green Deal goals and the formation of the environmental security system of the European region, is substantiated.
Keywords: environmental security, environmental taxation, environmental policy, ecological growth, green taxation, tax policy, tax administration, Green Deal, regulatory instruments, behavioral influences, globalization, risks